176k views
5 votes
Follow the steps to solve the equation using the algebra tiles. −4x + (−3) = –x + 3. 1. Add 4 positive x-tiles to both sides and create zero pairs. 2. Add 3 negative unit tiles to both sides and create zero pairs. 3. Divide the unit tiles evenly among the x-tiles. x =

User Datenshi
by
5.6k points

2 Answers

5 votes

Answer:

-2

Explanation:

:)))

User Ryan Allen
by
5.6k points
5 votes
X= negative 2

First take negative 4 and add it to both sides to get -3=3x+3
Then subtract 3 from both sides to get -6=3x
next divide -6 by 3x to get x= -2
User Uri Barenholz
by
5.8k points